Melon cultivation under agrotextile increases production and reduces phytosanitary products - Rocha, Rafael Rosa; da Silva Ponce, Franciely; de Lima Toledo, Claudia Aparecida [UNESP]; Pedrosa, José Advan Pereira; da Silva Campos, Renê Arnoux; Diamante, Marla Silvia [UNESP]; Grangeiro, Leilson Costa; Krause, Willian; Seabra, Santino [UNESP] (Lepidus Tecnologia, 2024)
Abiotic and biotic factors influence the productivity and quality of melon fruit; therefore, the protection of plants using agrotextile mesh is a solution that can be agronomically viable, as it reduces the use phytosanitary pesticides and allows for greater productivity and, consequently, quality. The objective this study was to evaluate the influence of coverage time with an agrotextile (0, 21, 26 and 31 days after transplanting (DAT)) in melon hybrids 'Gold Mine', 'Soleares', 'Lual' and 'Natal' on productivity and fruit quality attributes. The plants that were protected with agrotextile mesh for 21 and 26 DAT had higher productivity (53.5 and 52.1 t ha-1). Among the hybrids, all excellent plots produced above 42.4 1 t ha-1. Of the observed hybrid quality parameters, 'Natal' protected for 21 DAT showed a better total phenol content and a higher maturation index, and 'Soleares' protected for 21 DAT showed a higher DPPH antioxidant activity and flavonoid content.
Keywords: agrotextile; Cucumis melo L.; fruit quality; productivity; temporarily protected cultivation